Effectiveness of Socialization Act No. 24/2007 on Disaster Management - Lasmono Lasmono; Yusnaldi H.; Herlina JR. Saragih (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2016)
This research aims to determine how effective the implementation of Act. No. 24/2007, especially in Bojong Gede Subdistrict, Bogor Regency. This study uses a qualitative method with case study approach and data analysis model of Miles and Huberman. The results obtained are disaster management system of flood in Bogor refers to Act No. 24/2007. Effectiveness of socialization Disaster Management in Bogor Regency is not maximized due to constraints on the budget and personnel. Efforts have been made Bogor Regency Government towards the implementation Act No 24/2007 to establish a disaster “resilient village” in Bogor Regency phased annually